An Association between Pledging Policies and the Financial Performance of Cassava Product Manufacturers - Vongsomtakul, Trinuj; Buddhakulsomsiri, Jirachai; Parthanadee, Parthana (KnE Life Sciences, 2018)
This paper involves a study to investigate the association between pledging policies by the government and financial performance of cassava product manufacturers in Thailand. A polynomial regression model is constructed to describe a key financial performance measure using a set of control variables and pledging policy variables. The control variables are obtained from financial statements of 58 starch manufacturers and 8 ethanol manufacturers that solely use fresh cassava roots as raw material during 2009-2014. Result from the model suggests an appropriate agricultural policy for the cassava product industry in Thailand. Keywords : Cassava; Control Variables; Financial Performance; Pledging Policies, Polynomial Regression